Identify the first step in solving this equation for x : −3 = x4 + 2 .(1 point)
Responses
Multiply both sides by 2.
Multiply both sides by 2.
Subtract 2 from both sides.
Subtract 2 from both sides.
Add 2 to both sides.
Add 2 to both sides.
Divide both sides by 4.
9 answers
Subtract 2 from both sides.
What is the solution of the equation 10z − 6 = 24 solving for z ?(1 point)
Responses
0.4
0.4
−3
negative 3
1.8
1.8
3
Responses
0.4
0.4
−3
negative 3
1.8
1.8
3
3
Jonny is solving this equation for n : 8 + 3n = 20 . His first step is to subtract 8 from both sides of the equation. Why?(1 point)
Responses
8 is the first term in the equation.
8 is the first term in the equation.
He needs to follow the order of operations.
He needs to follow the order of operations.
He needs to reverse the order of operations.
He needs to reverse the order of operations.
8 is attached to 3n by subtraction.
Responses
8 is the first term in the equation.
8 is the first term in the equation.
He needs to follow the order of operations.
He needs to follow the order of operations.
He needs to reverse the order of operations.
He needs to reverse the order of operations.
8 is attached to 3n by subtraction.
8 is the first term in the equation.
Samuel is solving an equation for y . His first step is to add 7 to both sides. Which equation is he solving?(1 point)
Responses
2y + 15 = 7
2 y plus 15 equals 7
2y + 7 = 15
2 y plus 7 equals 15
2y − 7 = 15
2 y minus 7 equals 15
2y − 15 = 7
2 y minus 15 equals 7
Responses
2y + 15 = 7
2 y plus 15 equals 7
2y + 7 = 15
2 y plus 7 equals 15
2y − 7 = 15
2 y minus 7 equals 15
2y − 15 = 7
2 y minus 15 equals 7
2y + 7 = 15
Kelia is solving an equation for x . Her second step is to multiply both sides of the equation by 4. Which equation is she solving?(1 point)
Responses
4 + x6 = 1
4 plus Start Fraction x over 6 End Fraction equals 1
6 + x4 = 1
6 plus Start Fraction x over 4 End Fraction equals 1
4 + 6x = 1
4 plus 6 x equals 1
6 + 4x = 1
Responses
4 + x6 = 1
4 plus Start Fraction x over 6 End Fraction equals 1
6 + x4 = 1
6 plus Start Fraction x over 4 End Fraction equals 1
4 + 6x = 1
4 plus 6 x equals 1
6 + 4x = 1
6 + 4x = 1